The Role of Diet, Physical Activity, and Lifestyle in Alzheimer’s Disease Prevention: A Literature Review - Bogucka, Adrianna; Kotkowiak, Agata; Knychalska, Karolina; Łabuda, Mikołaj; Sowińska, Teresa; Szema, Agnieszka; Mentel, Oliwia; Słojewska, Aleksandra; Sikora, Jakub; Królikowska, Klaudia (Journal of Education, Health and Sport, 2025)
Alzheimer’s disease is currently the most common cause of dementia worldwide, primarily affecting older individuals. By impairing cognitive abilities, it significantly diminishes the quality of life of patients. Predictions indicate that its incidence will rise dynamically over the coming years due to population aging. To date, no treatment has been developed that addresses the underlying causes. As a result, increasing attention has been given to identifying factors that could prevent the development of the disease. This paper examines the literature analyzing the impact of lifestyle, diet, and physical activity on the prevention of Alzheimer’s disease. Positive lifestyle factors that have been repeatedly analyzed for their preventive value include, among others: a high level of education, engagement in pro-cognitive activities, social bonding, a healthy diet, and physical activity exceeding 150 minutes per week. All of the above have shown correlations with a lower incidence of Alzheimer’s disease, although not all researchers are certain about the positive impact of physical activity. Notably, higher education and its associated cognitive reserve theory, as well as the impact of the MIND and Mediterranean diets on inhibiting the inflammatory process, stand out. Currently, loneliness, smoking, obesity, diabetes, and hypertension may account for up to half of Alzheimer’s cases. Focusing on a single element influencing the development of Alzheimer’s disease is less important than combining multiple factors, such as an appropriate diet, regular physical activity, and social and cognitive engagement while avoiding recognized risk factors. Only this approach may help reduce millions of cases of dementia in the future.